PENGARUH ADMINISTRASI PENDIDIKAN BAGI DISIPLIN KERJA GURU DI SDN LENGGAHSARI 02 KECAMATAN CABANGBUNGIN BEKASI - Joni Tesmanto; Firman Ardiansyah (Pusat Riset dan Inovasi Nasional, 2022)
In the Lennggahsari 02 State Elementary School, Kecamatan Cabangbungin, Kabupaten Bekasi, there were problems that started from the teacher's work discipline that needed to be improved. This is indicated by the existence of overlapping work activities, delaying some activities, limited management to innovate and the unintegrated work team of teachers. In terms of personnel, it can be seen that there are problems such as: There are teachers who come late from the appointed time, there are teachers who go home before the end of school hours, there are teachers who are not present without giving a clear reason. The existence of the above teacher discipline constraints can be caused by various factors, such as: Leadership, Planning, Directing, Coordination, Educational Administration, Organizational Culture, Organizational Behavior, Salary System, Position Promotion, Educational Background and Family. In this study, the author tries to examine work discipline in relation to educational planning and administration. The method used in this study is descriptive associative survey method. In this method there are at least two variables. This associative research is a relationship between two variables, namely education administration and teacher work discipline. Based on the formulation of the results of the research at the Lenggahsari State Elementary School 02 Lenggahsari Village, Branchbungin District, it is presented that there is a positive relationship between the Education Administration Variable (X) and the Teacher Work Discipline Variable (Y). The higher the value of Education Administration, the Discipline of Teacher Work will increase.